Comparison of manual and automatic (MagNA Pure) isolation methods of total RNA from adipose tissue - Lacinova, Zdenka; Dolinkova, Marketa; Haluzikova, Denisa; Krajickova, Jana; Haluzik, Martin (Molecular biotechnology, 2008)
AIM: Comparison of manual and automatic (MagNA Pure) isolation methods of total RNA from adipose tissue with respect to its quality and recovery factor. MATERIAL: 120 human subcutaneous adipose tissue samples (about 100 mg/sample) were collected from patients during surgical operations. The tissue sample was stabilized in RNAlater (QIAGEN GmbH, Germany). METHODS: Total RNA was extracted by the following kits: Rneasy Protect Mini, Rneasy Lipid Tissue (QIAGEN GmbH, Germany) and MagNA Pure Compact RNA Isolation (Tissue) for MagNA Pure Compact Instrument (Roche Diagnostics GmbH, Germany). RESULTS: The average RNA yields with Rneasy Lipid Tissue kits were about two-fold higher in comparison with the Rneasy Protect Mini kit. When the MagNA Pure Compact System was used, RNA yields from the same sample were more uniform compared with manual systems. It was also more convenient and less time-consuming than the manual approach. No DNA contamination of total RNA samples was detected except for samples isolated by Rneasy Protect Mini Kit. CONCLUSION: Rneasy Lipid Tissue Kit and MagNA Pure Compact RNA Isolation Kit (Tissue) provide RNA samples of high quantity, purity and PCR amplificability. RNA samples are suitable for further processing using methods of molecular biology.
Keywords: molekulární biologie; tuková tkáň; polymerázová řetězová reakce s reverzní transkripcí; Humans; DNA, Complementary; Molecular Biology; lidé; RNA; Leptin; komplementární DNA; Adipose Tissue; Reverse Transcriptase Polymerase Chain Reaction; leptin